Cancer Management in Man: Chemotherapy, Biological Therapy, Hyperthermia and Supporting Measures - Minev, Boris R.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
This book represents a comprehensive description and evaluation of the most up-to-date approaches to cancer management. Each chapter, prepared by leading basic researchers and clinicians, provides an in depth description of a specific method for cancer management. The chemotherapy section of the book is updated to include the newest drugs as well as those currently in development. Organized by drug class, this section provides the latest information on most drugs, including their mechanisms of action, interactions with other agents, toxicities, side effects, and mechanisms of resistance. The biological therapy section of the book provides expanded coverage of the currently used cytokines, vaccines, and cell based therapies of cancer. Full consideration is also given to other modern treatment approaches, such as tyrosine kinase inhibitors, inhibitors of tumor angiogenesis, and the transcatheter management of cancer. Current advances in hyperthermia in cancer treatment, hematologic and nutritional support, bone marrow transplantation, pain management and care of the terminally ill patients with cancer are also presented. In summary, this book provides a comprehensive coverage of the current knowledge on the most innovative, systematic and multidisciplinary approaches to the treatment of patients with cancer.
Keywords: Medicine; Oncology; Biomedicine; Cancer Research; Oncology